O recuo de áreas úmidas na chapada do rio Uberabinha, MG: causas e implicações ambientais - Carvalho Neto, Luciano Marajó de (2022)
The wetlands in the region of the upper course of the Uberabinha river basin have reduced as a result of agricultural and livestock expansion. The fact that these areas have lost space results in the loss of quality and quantity of water resources, in addition to changing the ecological balance of the region. In this context, the present study aims to identify and quantify the decreases in wetlands in the region of the upper course of the Uberabinha river basin through the comparison of orbital images from the years 1964, 1979, 2002 and 2020, having as a product the maps of land use and occupation of the hydrographic basin for the mentioned years. Various anthropic uses were identified in wetlands, such as forestry, irrigated annual crops, non-irrigated crops and mining, totaling a 42.77% reduction in the quantity of wetlands in the upper course of the Uberabinha river basin between 1964 and 2020. Within the parameters analyzed, the water flow indicated a negative correlation in the dry period, tending to a reduction (Person: -0.3321, p-value 0.034) between the period from 1981 to 2019, while the average annual temperature showed a correlation positive increase (Person: 0.87, p value: 3.06.10-11) between 1979 and 2020 and total annual precipitation indicated a negative correlation (Person: -0.3439, p-value: 0.0464), tending to decrease between 1979 and 2020. The loss of wetlands and the reduction in flow in the study area are associated with changes in land use.